INNOVATION IN USING BETEL LEAVES IN PERSONAL HYGIENE EDUCATION TO IMPROVE BOYS' HEALTH AT PAUD AL-WALIDAH, GARUT DISTRICT - Nurjaman, Iman; Rinjani , Santi; Dewi, Winasari; Ainurrahmah, Yusni; Jinan, Ridwan Riadul; Yulianie, Rany; Sutrisno, Nisa Wening Asih; Bastian, Yani Annisa Fauziah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
This program focuses on personal hygiene education for boys at PAUD Al-Walidah, Sukajaya, Garut Regency. Through innovation in the use of betel leaves as a natural antiseptic ingredient by involving parents, this program aims to increase awareness and clean living behavior in children. Apart from that, this program is also designed to empower the community by opening business opportunities based on local innovation. The results of this activity show an increase in the ability and knowledge of parents of uncircumcised boys regarding the importance of keeping personal areas clean. Therefore, parents can use natural media using betel leaves which are processed into an antiseptic spray and the ingredients are available around the house to clean the scalp area of ​​their child's penis to prevent phimosis.